Self-reported halitosis and associated factors among older adults: A cross-sectional study - Laura Barreto Moreno; Paulo Roberto Graffiti Colussi; Milena Giotti Marostega; Nathália Prigol Rosalen; Cassiano Kuchenbecker Rösing; Francisco Wilker Mustafa Gomes Muniz (Elsevier, 2022)
Background: Population-based studies assessing the prevalence and associated factors of halitosis among older adults are scarce. Objectives: To evaluate the prevalence of self-reported halitosis and associated factors among older adults. Method: ology: Individuals aged ≥60 years were included. The main outcome was self-reported halitosis. Exposure variables were age, sex, skin color, level of education, marital status, presence of systemic health problems, use of medication, smoking exposure, alcohol exposure, access to dental care, toothbrush frequency, use of dental floss, number of present teeth, use of and need for dental prosthesis. Associations between the outcome and independent variables were performed with Poisson regression models with robust variance (p < 0.05). Results: A total of 569 older adults were included, of which 35.5% (n = 202) self-reported halitosis. In the final multivariate model, higher age (prevalence ratio [PR]:0.967; 95% confidence interval [95%CI]:0.946-0.988) and level of education (PR:0.673; 95%CI:0.469-0.967 and PR:0.635; 95%CI:0.414-0.973 for medium and high level of education, respectively, compared to low level) were associated with halitosis. Conversely, no access to dental care (PR:1.322; 95%CI:1.044-1.676) and a higher number of teeth present (PR:1.023; 95%CI:1.009-1.037) were associated with a higher occurrence of self-reported halitosis. Conclusion: A high prevalence of self-reported halitosis was detected among older adults and was associated with lower age, lower level of education, no access to the dentist and higher number of teeth present.